The Impact of Botanical Marinades on the Shear Force Value and Water Holding Capacity of Goat Meat - Tasnin Hunin AbdElwhab Mohamed; Juni Sumarmono; Fani Evadewi (Journal of Sustainable Livestock, 2026)
The context of goat meat production highlights the need for processing methods that improve texture and water quality without synthetic additives. Botanical marinations, involving herbal and spice extracts, are known to affect the physical and chemical parameters of meat, but their effects on shear force and water holding capacity (WHC) in goat meat remain poorly understood. The objective of this study was to evaluate the effect of botanical marinations on the shear force and WHC of goat meat and to develop a machine learning-based predictive model to link the botanical chemical composition and treatments to these quality parameters. The methodology used included marination treatments with various botanical extracts (e.g., herbal and spice extracts) injected and soaked for 24 hours, followed by measurement of shear force using Instron and WHC through centrifugation. The dataset, consisting of 150 goat meat samples from various treatments, was analyzed using Random Forest, SVM, and Neural Networks algorithms with 10-fold cross-validation, as well as metrics such as accuracy, precision, recall, and F1-score. The results showed that botanical marination significantly reduced shear force by 12% (p < 0.05) and increased WHC by 8-15% (p < 0.01), with phenolic components and organic acids as the main predictors. The Random Forest model achieved a prediction accuracy of 95.2%, outperforming other algorithms by 8-12%. These findings confirm that botanical marination effectively improves tenderness and water-holding capacity of goat meat, and provide a scientific basis for the development of high-quality meat products based on natural ingredients.